Life After Lead: Effects of Early Interventions for Children Exposed to Lead - Stephen B. Billings; Kevin T. Schnepel (Institute of Labor Economics (IZA), 2017)
Lead pollution is consistently linked to cognitive and behavioral impairments, yet little is known about the benefits of public health interventions for children exposed to lead. This paper estimates the long-term impacts of early-life interventions (e.g. lead remediation, nutritional assessment, medical evaluation, developmental surveillance, and public assistance referrals) recommended for lead-poisoned children. Using linked administrative data from Charlotte, NC, we compare outcomes for children who are similar across observable characteristics but differ in eligibility for intervention due to blood lead test results. We find that the negative outcomes previously associated with early-life exposure can largely be reversed by intervention.
Keywords: I12; I18; I21; J13; J24; K42; Q53; Q58; 330; lead exposure; early health shocks; early childhood intervention; human capital formation